2014
DOI: 10.1016/j.jsb.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Light- and Electron Microscopy with chemical tags

Abstract: Correlative microscopy incorporates the specificity of fluorescent protein labeling into high-resolution electron micrographs. Several approaches exist for correlative microscopy, most of which have used the green fluorescent protein (GFP) as the label for light microscopy. Here we use chemical tagging and synthetic fluorophores instead, in order to achieve protein-specific labeling, and to perform multicolor imaging. We show that synthetic fluorophores preserve their post-embedding fluorescence in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 34 publications
0
77
0
Order By: Relevance
“…Furthermore, super-resolution fluorescence imaging enables higher labeling efficiencies than immunogold EM using fluorophore-tagged antibodies, which facilitates structure determination by localization microscopy. Thus, localization microscopy and EM are complementary methods that can be combined to determine molecular positions in the context of the cellular ultrastructure provided by EM with nanometer resolution (Betzig et al, 2006;Watanabe et al, 2011;Kopek et al, 2012;Nanguneri et al, 2012;Suleiman et al, 2013;Sochacki et al, 2014;Perkovic et al, 2014). In order to perform correlative localization and electron microscopy, several methodological requirements have to be fulfilled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, super-resolution fluorescence imaging enables higher labeling efficiencies than immunogold EM using fluorophore-tagged antibodies, which facilitates structure determination by localization microscopy. Thus, localization microscopy and EM are complementary methods that can be combined to determine molecular positions in the context of the cellular ultrastructure provided by EM with nanometer resolution (Betzig et al, 2006;Watanabe et al, 2011;Kopek et al, 2012;Nanguneri et al, 2012;Suleiman et al, 2013;Sochacki et al, 2014;Perkovic et al, 2014). In order to perform correlative localization and electron microscopy, several methodological requirements have to be fulfilled.…”
Section: Introductionmentioning
confidence: 99%
“…Second, protein positions determined by localization microscopy have to be located within the EM image across large areas with a precision in the nanometer range. This demand is impeded by a lack of suitable alignment markers that are stationary at the nanoscale range and exhibit good contrast in the two imaging modes (Watanabe et al, 2011;Kopek et al, 2012;Sochacki et al, 2014;Perkovic et al, 2014). Even when such types of markers are available, structural deformations occurring between the two imaging modes can aggravate the overlay of the two images with molecular precision.…”
Section: Introductionmentioning
confidence: 99%
“…In the embedded tissues, the fluorescent intensity of fluorophores further depends on the resin types and embedding modes [19][20][21][22][23]. In this study, we labeled the brain slices with the same type of primary antibody (anti-TH) and the same type of secondary antibodies with commonly used fluorescent dyes, and embedded the slices in GMA/Lowicryl HM20/LR White resins.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, whether the whole-mount immunolabelling method is compatible with plastic embedding should be examined first, as plastic embedding of the sample is a pre-requisite to enable precise and ultra-thin slicing. In fact, plastic embedding has been applied to immunolabelled thin samples like cells and tissues [19][20][21][22], and could improve the axial resolution of immunolabelled sections [23]. However, procedures and resins for immunostaining and embedding the thin sample are unsuitable for large-volume sample.…”
Section: Introductionmentioning
confidence: 99%
“…2 In combination with techniques like stimulated emission depletion (STED) microscopy 3 and photoactivated localization microscopy (PALM), 4 fluorescent proteins can even offer super-resolved LM images. 5 Recently, Perkovic et al 6 reported an elegant method to perform direct stochastic optical reconstruction microscopy (dSTORM) [7][8][9] super-resolution LM on resin sections using in-section fluorescence of uranyl acetate-resistant chemical tags. This resulted in achieving high x-and y-resolution of the fluorescent signals.…”
Section: Introductionmentioning
confidence: 99%